Analyzing students’ computational thinking and math reasoning via PISA-based learning - Widodo, Mutiara Annisa; Marsigit, Marsigit; Pranowo, Galih (Jurnal Inovasi Teknologi Pendidikan, 2025)
omputational thinking and mathematical reasoning abilities are crucial 21st century skills. However, the results of international studies show that these abilities are still low in Indonesian students. This study aims to test the effectiveness of PISA-based learning in improving the computational thinking and mathematical reasoning abilities of junior high school students.  The PISA Principles are a learning guide released by the OECD to produce globally competent students. The study used a quasi-experimental design with two groups of grade VII junior high school students as subjects. The experimental group received a contextual-based PISA principle learning method, while the control group followed the conventional learning method. The research instrument was a computational thinking and mathematical reasoning ability test. Data were analyzed using a two-sample t-test. The results showed that the contextual-based PISA principle learning method was effective in improving students' mathematical reasoning abilities but was less effective for computational thinking abilities. These findings can be a reference in designing mathematics learning relevant to the demands of the 21st century.  The recommendation from the results of this study is the need for instrument adaptation to measure the dimensions of computational thinking that are more specific to the four main indicators, namely: decomposition, pattern recognition, abstraction and algorithms.